Typifications and three new synonymies in Evolvulus L. (Convolvulaceae-Cressae) - Santos, Diego; Da Silva, Marcos José; Buril, Maria Teresa (Phytotaxa, 2023)
Evolvulus comprises approximately 100 American species and is one of the largest genera in Convolvulaceae; it includes taxa that are sometimes difficult to identify; some of them have typification and taxonomic problems. Both nomenclatural and taxonomic issues were detected during the ongoing taxonomic treatment of the Evolvulus species from the northeastern region of Brazil. This study was conducted with a comprehensive protologue analysis, study of herborized specimens, including types, observation of populations in the field, and morphological analysis. From our conclusions, five lectotypifications, one second-step lectotypification, one neotypification for E. luetzelburgii and three new synonyms are proposed herein.